Advancing learning through gamification in primary schools: a systematic literature review - Ismu Sukamto; Irman Syarif; Tiyas Abror Huda; Gusniyati Buhari (Universitas Muhammadiyah Enrekang, 2025)
Gamification contributes positively to increased learning motivation, academic achievement, and 21st century skill development. However, the existing literature tends to be fragmented based on disciplines, types of games, or specific aspects of learning outcomes. This study aims to systematically examine the application of gamification in learning in elementary schools and its impact on students' learning motivation, academic achievement, and skill development. Through the Systematic Literature Review approach, this article analyzes 15 selected empirical research articles obtained from the Scopus and ScienceDirect databases. The results of the analysis show that gamification, both in digital and physical form, consistently improves the motivation, learning outcomes, as well as social, motor, and cognitive skills of elementary school students. Factors supporting success include teacher readiness, student enthusiasm, and infrastructure availability, while key barriers include technology limitations, time, and training. The study also found that gamification has high potential to be strategically integrated into the primary school curriculum. Thus, gamification can be a relevant, adaptive, and transformative pedagogical approach in 21st-century primary education.